Paracrine activity of Smurf1-silenced mesenchymal stem cells enhances bone regeneration and reduces bone loss in postmenopausal osteoporosis - Alberto González-González; Itziar Álvarez-Iglesias; Daniel García-Sánchez; Monica Dotta; Ricardo Reyes; Ana Alfonso-Fernández; Alfonso Bolado-Carrancio; Patricia Díaz-Rodríguez; María Isabel Pérez-Núñez; José Carlos Rodríguez-Rey; Jesús Delgado-Calle; Flor M. Pérez-Campo (Stem Cell Research & Therapy)
Abstract Background Osteoporosis (OP), characterized by reduced bone mass and mineral density, is a global metabolic disorder that severely impacts the quality of life in affected individuals. Although current pharmacological treatments are effective, their long-term use is often associated with adverse effects, highlighting the need for safer, more sustainable therapeutic strategies. This study investigates the pro-osteogenic and anti-resorptive potential of the secretome from Smurf1-silenced mesenchymal stem cells (MSCs) as a promising cell-free therapy for bone regeneration. Methods Conditioned media (CM) from Smurf1-silenced rat (rCM-Smur1) and human MSCs (hCM-Smurf1) was collected and analyzed. Pro-osteogenic potential was assessed by measuring in vitro mineralization in human and rat MSCs cultures. In vivo, studies were conducted using a rat ectopic bone formation model and a post-menopausal osteoporotic mouse model. Additionally, primary human osteoporotic MSCs were preconditioned with hCM-Smurf1, and their osteogenic capacity was compared to that induced by BMP2 treatment. Ex vivo, human bone explants were treated with hCM-Smurf1 to assess anti-resorptive effects. Proteomic analysis of the soluble and vesicular CM fractions identified key proteins involved in bone regeneration. Results CM from Smurf1-silenced MSCs significantly enhanced mineralization in vitro and bone formation in vivo. Preconditioning human osteoporotic MSCs with hCM-Smurf1 significantly increases in vitro mineralization, with levels comparable to those achieved with BMP2 treatment. Additionally, in ex vivo human bone cultures, treatment with hCM-Smurf1 significantly reduced RANKL expression without affecting OPG levels, indicating an anti-resorptive effect. In vivo, CM from Smurf1-silenced MSCs significantly increased bone formation in a rat ectopic model, and its local administration reduced trabecular bone loss by 50% in a post-menopausal osteoporotic mouse model after a single administration within just four weeks. Proteomic analysis revealed both soluble and vesicular fractions of hCM-Smurf1 were enriched with proteins essential for ossification and extracellular matrix organization, enhancing osteogenic differentiation. Conclusions The Smurf1-silenced MSCs' secretome shows potent osteogenic and anti-resorptive effects, significantly enhancing bone formation and reducing bone loss. This study provides compelling evidence for the therapeutic potential of Smurf1-silenced MSC-derived secretome as a non-toxic and targeted treatment for osteoporosis. These findings warrant further in vivo studies and clinical trials to validate its therapeutic efficacy and safety.